Open model of education using Open Source principles - Viduka Dejan; Ličina Boris; Kraguljac Vladimir (Trendovi u Poslovanju)
The information society is a force that has changed the way we live, work, learn, inform and have fun today. The open model of education has experienced explosive growth in the last decade thanks to the increasing availability of modern technologies. The Open Access Initiative can now be seen in many areas of education and science where it contributes to faster and better acquisition and dissemination of knowledge. This paper discusses the possibilities of using a new open model based on the principles of Open Source. The scientific contribution represents opportunities for application and improvement for all actors in the process, while creating significant financial savings and impact on the digital divide. This is reflected in the use of legal software that is free, the use of old computer configurations and open access to scientific and university publications. In this way, schools, teachers and students have the opportunity to participate in teaching, work or play, regardless of their financial status.